The acute effect of caffeine supplementation on strength, repetition sustainability and work volume of novice bodybuilders - Hamid Arazi; Nazanin Dehlavinejad; Roghayyeh Gholizadeh (Turkish Journal of Kinesiology, 2019)
Ergogenic effects of caffeine on anaerobic maximal and submaximal peak performance, especially in resistance exercise is not clear. According to this, the purpose of this study was to investigate the acute effect of moderate amounts of caffeine on maximal strength, repetition sustainability and work volume in the upper and lower body of novice body builders. In a randomized double blind study, 15 male body builders' athletes (age of 21.16±3.9 years, height of 174.42±6.12 cm and weight of 73.25±6.71 kg) were examined. Exercise protocol was to test one repetition maximum (1RM) in the bench press and leg press and repetition sustainability of bench press and leg press with 80% 1RM in 5 sets. These tests were performed, one hour after ingesting caffeine (6 mg/kg) and placebo, in two separate sessions as similar. Muscle strength, sustainability of repetitions and volume of work (load × the number of repetitions) of upper and lower body were measured. To examine the differences between the effects of caffeine and placebo, t-test was used. The results showed that caffeine causes a significant increase in the strength of the upper and lower body (P<0.05). The repetition sustainability of upper and lower body in the first, second and third sets did not change significantly, but decreased significantly in the fourth and fifth sets. In addition, volume of work at the first to fifth set with consumption of caffeine in the body was significantly more than placebo (P<0.05). However, in the first and second set of lower body exercise was not observed significantly difference and meaningful difference was only seen in the third to fifth set between caffeine and placebo conditions (P<0.05). It seems that acute consumption of caffeine supplementation with ergogenic effect on maximal strength, sustainability of repetitions and the training volume in resistance exercise improve performance and possibly stimulate muscle for its development.